FORMATION OF SOCIAL RELATIONS IN PRESCHOOL CHILDREN (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the process of forming social relations in preschool children, focusing on the psychological, developmental, and educational factors that influence early socialization. Preschool is a critical stage for acquiring the skills of interaction, cooperation, and communication that form the basis of future social competence. During this period, children learn how to share, resolve conflicts, express emotions, and understand the perspectives of others. The article discusses the role of family, peers, and educators in shaping social relations, as well as the impact of play, language development, and cultural context.